Gender and welfare - Matud Aznar, María Pilar (2009)
Studies of gender and welfare show the relevance of social factors in women and men welfare. Those worldwide studies indicate that inequality is a threat for women health and welfare. Such inequality is based on violence of which they are victims of, as well as poverty that affects thousands of women; these seem to be the worst stress sources and the greatest threat to their welfare. However, as well as it happens in the study of any other gender difference, we cannot forget thatintra-group variability is higher that inter-group, and that at the moment of analyzing genderdifferences, we also have to take into account social context.